1998
DOI: 10.1128/mcb.18.10.5809
|View full text |Cite
|
Sign up to set email alerts
|

I-PpoI, the Endonuclease Encoded by the Group I Intron PpLSU3, Is Expressed from an RNA Polymerase I Transcript

Abstract: PpLSU3, a mobile group I intron in the rRNA genes of Physarum polycephalum, also can home into yeast chromosomal ribosomal DNA (rDNA) (D. E. Muscarella and V. M. Vogt, Mol. Cell. Biol. 13:1023-1033, 1993). By integrating PpLSU3 into the rDNA copies of a yeast strain temperature sensitive for RNA polymerase I, we have shown that the I-PpoI homing endonuclease encoded by PpLSU3 is expressed from an RNA polymerase I transcript. We have also developed a method to integrate mutant forms of PpLSU3 as well as the Tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 51 publications
(51 reference statements)
2
45
0
Order By: Relevance
“…This effect may be due to regulatory processes that inhibit all later steps in the maturation pathway when an early step (intron removal) is blocked. This is consistent with the finding that insertion of an unspliceable mutant intron derived from Pp.LSU3 into the rRNA gene of S. cerevisiae results in accumulation of two ITS2-containing 27S rRNA precursor species (21).…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be due to regulatory processes that inhibit all later steps in the maturation pathway when an early step (intron removal) is blocked. This is consistent with the finding that insertion of an unspliceable mutant intron derived from Pp.LSU3 into the rRNA gene of S. cerevisiae results in accumulation of two ITS2-containing 27S rRNA precursor species (21).…”
Section: Discussionmentioning
confidence: 99%
“…The 413 nucleotides (nt) intron is inserted after helix 69 in the large subunit rRNA (position 1925, E. coli numbering), a conserved region of the large subunit rRNA that directly contacts the small ribosomal subunit (Cate et al 1999). Lin and Vogt (1998) found that the Tetrahymena intron spliced efficiently in the yeast Saccharomyces cerevisiae, when transposed into the 25S rRNA gene at the position homologous to its natural splice junction in Tetrahymena. Cells remained viable when the intron was integrated into all of the chromosomal rDNA repeats, demonstrating that the spliced 25S rRNA was functional.…”
Section: In Vivo Splicing Is Linked To Rrnamentioning
confidence: 99%
“…cerevisiae strain INVSc2/TtLSU1 (MATa his3-D200 ura3-167 25S::TtLSU1) has the Tetrahymena group I intron integrated into every copy of the 25S rDNA on Chromosome XII (Lin and Vogt 1998), and was the gift of V. Vogt. For splicing assays, plasmids expressing the intron were transformed into strain BY4733 (MATa his3D200 leu2D0 met15D0 trp1D63 ura3D0).…”
Section: Yeast Strainsmentioning
confidence: 99%
See 2 more Smart Citations